71.5k views
5 votes
Number 11!!! Need help

Number 11!!! Need help-example-1
User Pacuna
by
5.5k points

2 Answers

4 votes

Answer:

...

Explanation:

y is 1/3 x x + 7 so:

3 times x + (2 times 1/3x + 7) = 6

first, 1/3x plus 7 is 7 1/3x, so 7 1/3x x 2 is 14 2/3x.

14 2/3x + 3x = 17 2/3x

So no, it doesn't equal 6.

The equation is:

3 x x + 2(1/3 + 7) = 6

?

User Dakur
by
5.6k points
3 votes


y = (1)/(3) x + 7 \\ \\ \\ 1. \: y = (x)/(3) + 7 \\ 2. \: y - 7 = (x)/(3) \\ 3. \: (y - 7) * 3 = x \\ 4. \: 3(y - 7) = x \\ 5. \: x = 3(y - 7) \\ \\ \: or \\ \\ 1. \: (1)/(3) x + 7 = y \\ 2. \: (1)/(3) x = y - 7 \\ 3. \: ( (1)/(3)x )/( (1)/(3) ) = (y - 7)/( (1)/(3) ) \\ \\ answer. \: x = 3y - 21 \\ \\ \\ \\ 3x + 2y = 6 \\ \\ 1. \: 3x = 6 - 2y \\ 2. \: x = (6 - 2y)/(3) \\ 3. \: x = (2(3 - y))/(3) \\ or \\ \\ 1. \: 3x = - 2y + 6 \\ 2. \: (3x)/(3) = ( - 2y + 6)/(3) \\ \\ answer. \: x = ( - 2)/(3) y + 2

User Ted Bigham
by
5.4k points